2021
DOI: 10.1016/j.nmni.2021.100922
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum procalcitonin level as a biomarker for disease severity in COVID-19 patients

Abstract: The pandemic of coronavirus disease 2019 (Covid-19) has infected millions of individuals around the globe. Forecasting the Covid-19 severity is essential and various biomarkers could be used to evaluate it. The current study was therefore aimed to evaluate the serum pro-calcitonin (PCT) level as a biomarkers for bacterial co-infection and disease severity in Covid-19 patients. A total of 430 Covid-19 positive individuals were examined in which 332 (77.2%) were male individuals while 98 (22.8%) were female indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Patients with severe COVID-19 are highly susceptible to superimposed bacterial, fungal, and viral infections, including ventilator-associated pneumonia and bloodstream infection, among others ( 29 , 30 ). As for systemic biomarkers of infection, procalcitonin is a predictor of disease severity ( 31 ), and can be useful to guide antimicrobial stewardship ( 32 , 33 ). Another study found an association between procalcitonin and mortality in COVID-19 patients more than 75 years old ( 34 ).…”
Section: Diagnostic and Prognostic Value Of Biomarkersmentioning
confidence: 99%
“…Patients with severe COVID-19 are highly susceptible to superimposed bacterial, fungal, and viral infections, including ventilator-associated pneumonia and bloodstream infection, among others ( 29 , 30 ). As for systemic biomarkers of infection, procalcitonin is a predictor of disease severity ( 31 ), and can be useful to guide antimicrobial stewardship ( 32 , 33 ). Another study found an association between procalcitonin and mortality in COVID-19 patients more than 75 years old ( 34 ).…”
Section: Diagnostic and Prognostic Value Of Biomarkersmentioning
confidence: 99%
“… Heesom et al 21 0.5 ng/mL Procalcitonin can be used as an Antibiotic Stewardship tool to de-escalate the use of antibiotics. Waris et al 14 0.25 ng/mL Procalcitonin (>0.25) is an indicator of bacterial coinfection in COVID-19 patients. Hughes et al 15 0.25 ng/mL 1- Procalcitonin (>0.25) is an indicator of bacterial coinfection in COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Procalcitonin (PCT), a precursor of the hormone calcitonin, is an important inflammatory biomarker that is synthesized mainly in response to bacterial infections, reflecting the extent of the systemic inflammatory response. Bacterial toxins are crucial in the induction of the synthesis of this protein, which is also stimulated by high levels of tumor necrosis factor (TNF-α) and interleukin-6 (IL-6), produced in response to infection [ 29 ]. Procalcitonin is considered a useful diagnostic marker, allowing to distinguish bacterial infection from viral infection and as a prognostic determinant of the severity of infection and effectiveness of applied antibiotic therapy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%